Impact of rising rice prices and policy responses in Mali : simulations with a dynamic CGE model - Nouve, Kofi (Policy research working paper, 2008)
"The increase in the international price of rice is likely to have substantial negative impacts on the poor in countries such as Mali which are net importers of rice. This paper relies on a dynamic CGE model to estimate the likely impact of the recent increase in rice prices on poverty with and without policy responses. Two sets of policy responses are considered: import tax cuts on rice and measures to increase productivity of domestic rice production. The results suggest that an increase in productivity would have a much larger positive impact than a reduction in taxes. "--World Bank web site